GAYA KEPEMIMPINAN, KESEHATAN KESELAMATAN KERJA (K3) DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN LPD DI KECAMATAN TAMPAK SIRING - Dewa Gede Artha Ariasa; Nengah Landra; Ni Made Dwi Puspitawati (VALUES, 2022)
This research aims to find out the influence of leadership style, occupational safety health (K3) and organizational culture on the performance of LPD employees in Kecama-tan Tampak Siring. The study took 35 respondents on LPD employees in Keca-matan Tampak Siring. The data is analyzed using multiple linear regression analysis techniques, then tested through classical assumption tests. The study was obtained through the results of the spread of questionnaires, then analyzed using the SPSS statistics application version 20 for Windows which was used to answer the problem formulation in the study. Test results on hypotheses show that variables: 1). The style of leadership has a positive and significant effect on employee performance, 2). Occupational health (K3) has a positive and significant effect on employee performance, 3). Organizational culture has a positive and significant influence on employee performance. Research advice is expected to always establish good relationships with fellow employees so as to improve the performance of the company while improving the company's performance.